Nanostarch based nanoencapsulation of Mucuna pruriens extract and its evaluation as anti-parkinsonian drug - Sardjono, Ratnaningsih Eko; Gunawan, Ramdhan; Kadarohman, Asep; Erdiwansyah, E.; Rizalman, Mamat; Melati, Khairuddean (Elsevier Ltd, 2024)
Parkinson's disease is a neurodegenerative disease caused by low dopamine levels in the brain. This study aims to obtain the optimum condition for M. pruriens extract nanoencapsulation in nano starch (NS-MPn) and nanostarch-maltodextrin (NS-MD-MPn), nanocapsules characteristics, and their potential as anti-Parkinsonian drug. The nanoencapsulation process was carried out by ultrasonic method. FTIR, SEM, and TEM carried out the characterization of NS-MPn and NS-MD-MPn nanocapsules. Encapsulation efficiency was evaluated by UV-Vis spectroscopy. SEM and TEM characterization NS-MPn and NS-MD-MPn nanocapsules have non-spherical surface morphology, spherical in shape 234.98 and 90.85 nm, respectively. NS-MPn have 21.35% encapsulation efficiency, meanwhile, NS-MD-MPn has 30.02%.